The Role of Health-Saving Technologies in the Work Practice of the Primary School Teacher - A. N. Semiletova (Открытое образование (Москва), 2023)
The purpose of the study: to study the theory and practice of applying health-saving technologies in the work of a primary school teacher; development of a system of lessons using health-saving technologies. Materials and methods. The following general theoretical and empirical research methods are used: analysis, synthesis, definition, study of scientific and theoretical literature, survey and questionnaire methods, pedagogical diagnostics.Results. At the present stage of development of society, an increasing number of negative phenomena are found in the lives of not only adults, but also children, which is supported not only by high rates of incidence, but also by the prevailing indexes of passivity, sedentary lifestyle that modern children and adolescents lead. The former approaches and strategies in the organization of life activity, which were approved by society in the period of post-industrial society, now reveal their own inconsistency, since a qualitative transition from one type of society to another is taking place in the world space. Accordingly, the content and nature of the conditions for the formation of children’s health in an educational organization also change. The authors of the article describe the results of the study of the role of health-saving technologies in the work of a primary school teacher. The main directions of work on the use of health-saving technologies are presented. Summary of these technologies is given. To determine the effectiveness of health-saving technologies in the practice of a primary school teacher, stating, forming and control experiments were organized. To determine the level of knowledge of students about a healthy lifestyle and its key components, the author’s test “Healthy lifestyle” was used. The research results are presented in the form of tables and diagrams.Conclusion. At present, it is safe to say that it is the teacher who is able to do more for the health of the modern student than the doctor. This does not mean that he should perform the duties of a medical officer. It is just that the teacher should work in such a way that schooling does not harm the health of students.The results of the control experiment proved that health-saving technologies helped to maintain and improve the health of students.